W co wierzą młodzi? Badania socjologiczne nad religijnością młodzieży studiującej w Warszawie - Tarnawskaja, Julia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The paper attempts to address a number of queries on religiousness of the Polish students, who are likely to constitute the new middle class soon. The author tries to present how their faith is related to other attitudes, beliefs, politics and morality. Is it still predominated by a traditional Catholic ritual, automatically inherited after older generations without any reflection, as it was before 1989? Is this Catholic faith still identified with being Polish and approached as a „political faith”? Or maybe some turbulent changes have taken place, enforced by new economic, political and social freedom or mass culture? The findings and conclusions presented in the paper are based on a survey conducted by the author in January 2001 among the students of theWarsaw University and the Warsaw School of Information Technology. They prove that mentality of the youth, who live in a large city and study, has already undergone a series of various transformations, some highly interesting, yet it is rather difficult to identify some radical changes or a religious and moral „revolution”. A common attempt at a compromise is also symptomatic here, the desire to harmonize the tradition, which is still lively and significant, with new experience provided by liberal democracy, mass culture or the spiritualism of New Age.